Activity, balance, learning, and exposure (ABLE): a new intervention for fear of falling. (4th January 2016) - Wetherell, Julie Loebach; Johnson, Kristen; Chang, Douglas; Ward, Samuel R.; Bower, Emily S.; Merz, Caroline; Petkus, Andrew J.
Abstract : Objective: Fear of falling is an important problem among older adults, even those with relatively low rates of objective fall risk, who are often overlooked as targets for intervention. Method: We developed and pilot tested a new intervention, Activity, Balance, Learning, and Exposure (ABLE), in a sample of 10 older adults with excessive fear of falling. The ABLE intervention integrates exposure therapy and cognitive restructuring with a home safety evaluation and an exercise program and is conducted in the home. In this pilot project, ABLE was jointly conducted by a physical therapist and a psychologist with expertise in geriatric anxiety disorders. Results: The intervention was feasible and acceptable and resulted in decreases in fear and activity avoidance for most participants. One participant experienced an injurious fall. Discussion: We learned a number of important lessons resulting in modifications to the inclusion criteria, assessments, and intervention over the course of this pilot study. Results suggest that ABLE has promise for treating excessive fear of falling in the elderly and support testing the intervention in a larger randomized trial. Copyright © 2016 John Wiley & Sons, Ltd.